Modern mathematical tools and techniques in capturing complexity - Pardo Llorente, Leandro; Balakrishnan, N. 1956-; Gil, María Á. (Maria-Ángeles) (Heidelberg, Germany Springer Berlin, 2011)
Real-life problems are often quite complicated and, for centuries, Mathematics has provided the necessary tools and ideas to formulate these problems mathematically and then help in solving them either exactly or approximately. This book aims to gather a collection of papers dealing with several different problems arising from many disciplines and some modern mathematical approaches to handle them. In this respect, the book offers a wide overview on many of the current trends in Mathematics as valuable formal techniques in capturing and exploiting the complexity involved in real-world situations. Several researchers, colleagues, friends and students of Professor María Luisa Menéndez have contributed to this volume to pay tribute to her and to recognize the diverse contributions she had made to the fields of Mathematics and Statistics and to the profession in general. She had a sweet and strong personality, and instilled great values and work ethics in her students through her dedication to teaching and research. Even though the academic community lost her prematurely, she would continue to provide inspiration to many students and researchers worldwide through her published wor
Part I Advanced Methods in Statistics -- Part II Applied Mathematics -- Part III Distribution Theory and Applications -- Part IV Divergence Measures and Statistical Applications -- Part V Modelling in Engineering Problems -- Part VI Theory of Games -- Part VII Model-Based Methods for Survey Sampling -- Part VIII Probability Theory -- Part IX Robust and Soft Methods in Statistics -- Part X Modelling in Biological and Medical Problems.
Electronic reproduction.
Keywords: Computational complexity